Association of maternal neutrophil-lymphocyte ratio with adverse perinatal outcomes in preterm premature rupture of membranes: a case-control study - Meena, Manisha K.; Gaur, Sindhu S.; Meena, Ram L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Preterm premature rupture of membranes (PPROM) is a significant contributor to preterm birth and is associated with both maternal and perinatal complications. Neutrophil lymphocyte ratio (NLR) is an emerging marker of systemic inflammation. This study was conducted to evaluate the association of maternal NLR with adverse maternal and perinatal outcomes in PPROM cases. Methods: This prospective case-control study was conducted among 60 pregnant women (30 PPROM cases with elevated NLR and 30 controls with normal NLR). Maternal NLR was calculated using complete blood count reports. Participants were grouped based on NLR levels and their association with maternal and perinatal outcomes were study. Results: The incidence of neonatal intensive care unit (NICU) admission was significantly higher among newborns in the case group (70%) compared to the control group (36.66%). Similarly, perinatal mortality was markedly elevated in the case group (70%) relative to the control group (13.33%), indicating an overall poorer perinatal outcome in the case group. Conclusion: Elevated maternal NLR is significantly associated with adverse maternal and perinatal outcomes in PPROM. It can serve as a simple and cost-effective inflammatory marker for risk stratification and early intervention.